2021
DOI: 10.1016/j.cognition.2021.104865
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup preference, not dehumanization, explains social biases in emotion attribution

Abstract: Psychological models can only help improve intergroup relations if they accurately characterise the mechanisms underlying social biases. The claim that outgroups suffer dehumanization is near ubiquitous in the social sciences. We challenge the most prominent psychological model of dehumanization - infrahumanization theory - which holds outgroup members are subtly dehumanized by being denied human emotions. We examine the theory across seven intergroup contexts in thirteen pre-registered and highly powered expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…Indeed, there is a substantial body of empirical research suggesting that we do attribute mental states, traits, and emotions to outgroup members. Whereas outgroup members might be thought of as lacking socially desirable human qualities such as warmth and rationality, they are often viewed as possessing undesirable human qualities, such as arrogance, spite, and jealousy to a greater extent than do the ingroup (Enock, Flavell, et al, 2021; Enock, Tipper, et al, 2021; Over, 2021a, 2021b). These findings accord with research on stereotype content showing that outgroups are often thought of as possessing negative yet uniquely human characteristics, such as being devious, deceptive, and cunning (Over, 2021b).…”
Section: What Is Pdt?mentioning
confidence: 99%
“…Indeed, there is a substantial body of empirical research suggesting that we do attribute mental states, traits, and emotions to outgroup members. Whereas outgroup members might be thought of as lacking socially desirable human qualities such as warmth and rationality, they are often viewed as possessing undesirable human qualities, such as arrogance, spite, and jealousy to a greater extent than do the ingroup (Enock, Flavell, et al, 2021; Enock, Tipper, et al, 2021; Over, 2021a, 2021b). These findings accord with research on stereotype content showing that outgroups are often thought of as possessing negative yet uniquely human characteristics, such as being devious, deceptive, and cunning (Over, 2021b).…”
Section: What Is Pdt?mentioning
confidence: 99%
“…The assumption is supported by research showing that people attribute more human emotions (or “secondary emotions,” referring mostly to sentiment) to ingroups than to outgroups, whom they deprive from this human essence (e.g., Leyens et al, 2001 , 2003 ; Cortes et al, 2005 ). In recent years, research has expanded to study infra-humanisation with respect to a variety of groups and characteristics, including age ( Boudjemadi et al, 2017 ), nationality ( Davies et al, 2018 ), or religion ( Banton et al, 2020 ), finding it to apply to a large set of possible categories (but see Enock et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent research has found that perspective taking and other explicit appeals to increase interracial prosociality can fall short in two ways (see Zaki & Cikara, 2015 for review). First, outgroup members' mental complexity is often misunderstood or neglected, both of which may promote reliance on stereotypes about their traits, goals, intentions, emotions, and behaviors (Enock et al, 2021;Leyens et al, 2000;Park & Judd, 1990;Rothbart & Taylor, 1992).…”
Section: Racial Outgroup Membermentioning
confidence: 99%